Phantom Tumor of the Lung: Localized Interlobar Effusion in Congestive Heart Failure - Mislav Lozo; Emilija Lozo Vukovac; Zeljko Ivancevic; Ivan Pletikosic (Case Reports in Cardiology)
Localized interlobar effusions in congestive heart failure (phantom or vanishing lung tumor/s) is/are uncommon but well known entities. An 83-year-old man presented with shortness of breath, swollen legs, and dry cough enduring five days. Chest-X-ray (CXR) revealed massive sharply demarked round/oval homogeneous dense shadow 10 × 7 cm in size in the right inferior lobe. The treatment with the loop diuretics and fluid intake reduction resulted in complete resolution of the observed round/oval tumor-like image on the control CXR three days later. Radiologic appearance of such a mass-like configuration in patients with congestive heart failure demands correction of the underlying heart condition before further diagnostic investigation is performed to avoid unnecessary, expensive, and possibly harmful diagnostic and treatment errors.